Quantitative single-protein imaging reveals molecular complex formation of integrin, talin, and kindlin during cell adhesion - Lisa S. Fischer (Nature Portfolio, 2021)
Single-molecule localisation microscopy is limited by low labeling and detection efficiencies of the molecular probes. Here the authors report a framework to obtain absolute molecular quantities on a true molecular scale; the data reveal a ternary adhesion complex underlying cell-matrix adhesion.